Global economic prospects. (World Bank Group flagship report., 2020)
Global growth is projected to be slightly faster in 2020 than the post-crisis low registered last year. While growth could be stronger if reduced trade tensions lead to a sustained reduction in uncertainty, the balance of risks to the outlook is to the downside. Growth in emerging market and developing economies is also expected to remain subdued, continuing a decade of disappointing outcomes. A steep and widespread productivity growth slowdown has been underway in these economies since the global financial crisis, despite the largest, fastest, and most broad-based accumulation of debt since the 1970s. In addition, many emerging market and developing economies, including low-income countries, face the challenge of phasing out price controls that impose heavy fiscal cost and dampen investment. These circumstances add urgency to the need to implement measures to rebuild macroeconomic policy space and to undertake reforms to rekindle productivity growth. These efforts need to be supplemented by policies to promote inclusive and sustainable long-term growth and accelerate poverty alleviation. Global Economic Prospects is a World Bank Group Flagship Report that examines global economic developments and prospects, with a special focus on emerging market and developing countries.